Altitudinal Distribution Patterns of Phyllosphere Microbial Communities and Their Contribution to Silage Fermentation of Kobresia pygmaea Along the Elevation Gradient on the Tibetan Plateau - Yang, Xin; Bao, Yuhong; Shao, Tao; Wang, Wenkang; Ma, Pengfei; Wang, Wenbo; Gallo, Antonio; Yuan, Xianjun (Frontiers in Microbiology, 2022)
The study was conducted to investigate altitudinal distribution pattern of phyllosphere bacterial and fungal community and to evaluate the contributions of the microbial community to the natural fermentation of Kobresia pygmaea on the Tibetan plateau. The K. pygmaea was collected from 2500, 3000, 4000, 4500, and 5000 m above sea level (a.s.l.) along the altitudinal gradient, and was ensiled for 60 d. In the fresh K. pygmaea (F), the phyllosphere bacterial diversity increased while fungal diversity decreased along the elevation gradient, bacterial and fungal richness showed a unimodal distribution, with peak abundance at 4000 and 3000 m a.s.l., respectively. After 60 d of ensiling, the bacterial and fungal composition significantly changed and did not exhibit clear altitudinal distribution patterns, the dominant genera in silages (S) were different among 5 elevations. All K. pygmaea underwent a weak fermentation indicated by pH above 5.0 and low ratio of lactic/acetic acid (LA/AA). The S5000 and S3000 showed the highest and the lowest pH, respectively. Although Lactobacillus dominated the S4000 after 60 d of ensiling, S4000 still exhibited poor fermentation quality as well as other silages of 4 regions. The higher ammonia N concentrations in S3000 and S4000 than other silages were consistent with the detectable butyric acid in S3000 and S4000. The natural fermentation of K. pygmaea collected from 5 regions exhibited poor fermentation quality, therefore, inoculating lactic acid bacteria to K. pygmaea before ensiling is highly recommended to improve fermentation quality on the Tibetan plateau.